ANALYSIS OF FACTORS ASSOCIATED WITH INDOOR AIR GERM COUNTS IN INPATIENT ROOMS AT ERNALDI BAHAR HOSPITAL - Menny Apriani; Akhmad Dwi Priyatno; Erma Gustina; Ali Harokan; Helmy Adriansyah (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
The air germ count in the inpatient room of Ernaldi Bahar Hospital tends to exceed the maximum concentration of the indoor air germ count index which is set at an average of above 500 CFU/m3. This condition has the potential to increase the risk of nosocomial infections, especially lower respiratory tract infections, which can have an impact on the safety of patients and medical personnel. Various physical environmental factors such as temperature, humidity, lighting, and building technical requirements as well as staff compliance in the implementation of hand washing are thought to play a role in influencing airborne germ counts in inpatient rooms. The main objective of this study was to find and analyze the variables that contribute to the air germ rate in the inpatient room of Ernaldi Bahar Hospital in 2025. The study was conducted of May 21 th – June 20 th, 2025.  The design of this study was quantitative with a cross-sectional study.  The population of this study were all psychiatric inpatients and nurse all psychiatric inpatients at Ernaldi Bahar Hospital, South Sumatra Province. The sample in his study totaling 45 inpatient rooms with  total sampling technique anda 45 nurse with purposive sampling . data collection and retricval was using a direct measurement and observation. Analysis used univariate, bivariate and multivariate.  The statistis test used an chi-square test and logistic regression with significance level (α) 0,05. The results showed taht room temperature (p value = 0,009), room humidity (p value = 0,012), room lighting (p value = 0,002), technical requirements of the room building (p value = 0,951), compliance with hand washing implementation (p value = 0,019). Multivariate statistical tests obtained the most dominant variable associated with indoor air germ numbers is lighting. In conclusion, there is a relationship between room temperature, humidity, room lighting and compliance with hand washing implementation with air germs in the inpatient rooms at Ernaldi Bahar Hospital.